Modifiable Cardiovascular Risk Factors in Hypertensive Patients - Ullah, Mohammad; Saha, Suman Kumar (Cardiovascular Journal, 2018)
Background: Hypertension is one of the most important noncommunicable diseases. Presence of other cardiovascular risk factors in hypertensive patients increases the risk of ischaemic heart disease and cerebrovascular diseases. We evaluated the prevalence of cardiovascular risk factors among the hypertensive patients. Methods: Patients presenting to the outpatient department of a secondary hospital were included in the study. The prevalence of diabetes mellitus, current smoking, family history of ishaemic heart disease, dyslipidaemia and nephropathy were evaluated. Results: A total of 144 patients were included in the study (male 66 & female 78). 29.8% patients were smoker (57% of male patients and 6% of female patients); 34% patients were diabetic; 27% patients had raised total cholesterol, 40.3% had reduced HDL, 22% had raised LDL, 36.8% had raised triglyceride and 33.3% patients had nephropathy (proteinuria/ raised serum creatinine). Conclusion: The prevalence of cardiovascular risk factors, specifically smoking, diabetes mellitus, raised LDL and nephropathy were more among the hypertensive patients. All the hypertensive patients should be evaluated for modifiable cardiovascular risk factors during diagnosis and follow up. Treatment of these risk factors can improve the prognosis of the hypertensive patients. Cardiovasc. j. 2018; 11(1): 10-16